Primary care for the Roma in Europe: Position paper of the European forum for primary care - de Graaf Pim; Rotar Pavlič Danica; Zelko Erika; Vintges Marga; Willems Sara; Hanssens Lise (Sciendo, 2016)
Roma populations' low health status and limited access to health services, including primary care, has been documented in many European countries, and warrants specific health policies and practices. A variety of experiences shows how primary care can adjust its practices to reduce the barriers to primary care for Roma populations.